Análisis comparativo del secretoma de Aspergillus brasiliensis cultivado en medio sólido con diferentes concentraciones de sacarosa - Nava del Villar, Silvia Guadalupe (Universidad Autónoma Metropolitana, 2016)
The present study compared the A. brasiliensis ATCC 9642 secretome obtained by submerged fermentation using the minimal medium Hill y Kafer with three initial concentrations of sucrose: 20, 40 and 60 g/L. The samples for the analysis of secretomes were taken at the culture time where the maximum rate of production of CO2 was observed, with this it was possible to obtained cultures with comparable physiological states. The extracellular protein extracts obtained were concentrated and diafiltered with membrane (10 KDa) and after that, the proteins were separated by their isoelectric point (isoelectrofocus) and their molecular weight (SDS-PAGE). The images obtained from the separation by 2D-PAGE were analyzed through the software PDQuest, identifying the reproducible spots between replicates. 28 spots were selected from the 2D-PAGE gels for their protein analysis. The proteins in the spots were digested with trypsin. The obtained peptides were analyzed by liquid chromatography coupled to mass spectrometry (LC-MS/MS). For the characterization of the sequences identified were used the next data bases: BlastP, AspGD, UniProt, ExPASy, KEGG, Pfam, SignalP y SecretomeP. A. niger CBS513.88 was considered as reference microorganism. 30 proteins were identified of which 15 participate in the carbohydrates metabolism, 5 in oxide reduction reactions, 2 has proteolytic activity, 2 has pathogenic function and the others six proteins have different function. It was showed that secretion of proteins decreased when the sucrose concentration in the media was increased, of these proteins that participate in the carbohydrates metabolism, glucoamylase was expressed at constitutive level and this was independent of the sucrose concentration. By another hand, it was observed that the abundance of invertasa was decreased when the sucrose concentration was increased.; El presente trabajo comparó el secretoma de A. brasiliensis ATCC 9642 obtenido en cultivo en medio líquido (CML) empleando el medio mínimo Hill y Kafer, con tres concentraciones de sacarosa inicial: 20, 40 y 60 g/L. Las muestras para análisis de los secretomas se tomaron en el tiempo de cultivo en que se alcanzó la tasa máxima de producción de CO2, lo que permitió su obtención en cultivos con estados fisiológicos comparables. Los extractos proteicos extracelulares obtenidos fueron concentrados y diafiltrados con membranas de 10 kDa y posteriormente, las proteínas fueron separadas por su punto isoeléctrico (Isoelectroenfoque) y después por sus pesos moleculares (SDS-PAGE). Las imágenes obtenidas de la separación en dos dimensiones (2D-PAGE) se analizaron con el software PDQuest, identificando los “spots” reproducibles entre replicas. De los geles 2D-PAGE se seleccionaron 28 “spots” para análisis de proteínas. Las proteínas en los “spots” fueron digeridas con tripsina. Los péptidos obtenidos fueron analizados por cromatografía líquida acoplada a espectrometría de masas (LC-MS/MS). Para la caracterización de las secuencias identificadas se emplearon las siguientes bases de datos: BlastP, AspGD, UniProt, ExPASy, KEGG, Pfam, SignalP y SecretomeP y se consideró como microorganismo de referencia A. niger CBS 513.88. Se identificaron 30 proteínas de las cuales 15 participan en el metabolismo de carbohidratos, 5 en reacciones de oxidación-reducción, 2 presentan actividad proteolítica, 2 tienen función de patogénesis y las seis proteínas restantes tienen diferente función. Se demostró que la secreción de proteínas disminuyó conforme aumenta la concentración de sacarosa en el medio, siendo la mitad de éstas, proteínas que participan en el metabolismo de carbohidratos entre las cuales la glucoamilasa se expresa a nivel constitutivo independientemente de la concentración de sacarosa mientras que la abundancia de invertasa disminuye cuando aumenta la concentración de sacarosa.